Instruments and Challenges of Corruption Diagnostics Around the World and in Lithuania - Piliponytė, Jolanta (Sociologija. Mintis ir veiksmas, 2006)
This article addresses the issue of corruption diagnostics. It analyses the existing approaches to measure corruption, namely the perception-based approach, the experience-based approach, the tracking approach and the legal statistics approach. The article discusses the possibilities and difficulties that measuring of corruption presents and offers global and national examples to illustrate that. It also addresses in greater detail corruption research carried out in Lithuania. Finally, the article presents the summary of the insights made, discusses the challenges of corruption diagnostics and its possible solutions.
Keywords: corruption; methodology; measurement of corruption